(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The economic downturn has caused fiscal tension in the country in recent years. Budget revenues decreased and it indicated the need for the revision and control of expenditure. Therefore, the issues related to the evaluation opportunities of governmental expenditure are becoming particularly urgent. It is emphasized that a key factor in public sector’s performance is the public good, which ensures services of government institutions, and encompasses both quantitative and qualitative aspects. However, economic researches on the public sector’s performance efficiency focus on problems related to the determination of the public good as well as activate the possibility for its practical application. The US economist W.A. Niskanen mathematically grounded the bureau performance balance-shaping principles in the context of possibilities for evaluation of public administration, id est. the situation in which the institution’s performance can be evaluated as effective. In order to evaluate efficiency aspects of the public sector’s performance as well as their potential impact on the formation process of the state budget spending part, the authors of the research put forward the following objective – to perform mathematical calculations of bureau performance balance-shaping principles, grounded by the US economist W. A. Niskanen, and to assess the model’s potential opportunities for practical application. As a research novelty, the developed practical application software of Niskanen’s classical model of bureau performance is presented in MATLAB environment.